Adsorptive removal of methylene blue dye onto sodium alginate/ polythiophene composite microbeads: Non-linear isotherm, kinetic, and thermodynamic study - Berk, Miray Eylul; Isik, Birol; Ugraskan, Volkan; Cankurtaran, Ozlem (ELSEVIER, 2025)
Polythiophene (PTh), a class of conductive polymers, has the potential to be an effective adsorbent due to its tunable characteristics, environmental stability, electron-rich structure, and so on. Though its efficiency has been proven in many applications, investigations into using PTh in adsorption studies are currently lacking. For the first time, this study examined the efficiency of sodium alginate (SA) matrix composites filled with PTh for dye removal by adsorption. First, PTh was synthesized using the oxidative chemical polymerization process, and SA composites with PTh in different weight ratios were produced. Methylene blue (MB), one of the most used dyes in the industry, was chosen as a model dye for adsorption studies. Adsorption experiments revealed that the best composite composition is 10 % PTh (SA-PTh-10), with optimal temperature = 298 K, pH = 6, contact time = 90 min, and adsorbent amount = 0.025 g/50 mL. The MB dye adsorption process was carried out using a pseudo-second-order kinetic model with non-linear regression coefficients (r2 = 0.9999). The non-linear Langmuir adsorption isotherm model is consistent with MB dye adsorption, indicating monolayer adsorption on the composite. According to the Langmuir adsorption isotherm model calculations, SA-PTh-10 microbeads have a maximum adsorption capacity of 134.32 mg/g. Furthermore, the Sips isotherm model shows that SA-PTh-10 composite microbeads have a high adsorption capacity of 104.37 mg/g. Exothermic and spontaneous adsorption of MB dye was revealed by the negative enthalpy (Delta Ho =-20.13 kJ/mol) and Gibbs free energy (Delta Go =-25.75 kJ/mol). Reusability study was conducted, and composite microbeads were observed to be effective for up to 7 cycles.
Keywords: Adsorption; Methylene blue; Polythiophene; Sodium alginate; AQUEOUS-SOLUTION; WASTE-WATER; HYDROGEL BEADS; CATIONIC DYES; EQUILIBRIUM; ADSORBENT; CLASSIFICATION; MECHANISM; BIOMASS; IONS; Biochemistry & Molecular Biology; Chemistry; Polymer Science